Adolescent girls' neural response to reward mediates the relation between childhood financial disadvantage and depression. (5th April 2015) - Romens, Sarah E.; Casement, Melynda D.; McAloon, Rose; Keenan, Kate; Hipwell, Alison E.; Guyer, Amanda E.; Forbes, Erika E.
<x xml:space="preserve">Abstract</x> Background Children who experience socioeconomic disadvantage are at heightened risk for developing depression; however, little is known about neurobiological mechanisms underlying this association. Low socioeconomic status (SES) during childhood may confer risk for depression through its stress‐related effects on the neural circuitry associated with processing monetary rewards. Methods In a prospective study, we examined the relationships among the number of years of household receipt of public assistance from age 5–16 years, neural activation during monetary reward anticipation and receipt at age 16, and depression symptoms at age 16 in 123 girls. Results Number of years of household receipt of public assistance was positively associated with heightened response in the medial prefrontal cortex during reward anticipation, and this heightened neural response mediated the relationship between socioeconomic disadvantage and current depression symptoms, controlling for past depression. Conclusions Chronic exposure to socioeconomic disadvantage in childhood may alter neural circuitry involved in reward anticipation in adolescence, which in turn may confer risk for depression.